Pengaruh Kecerdasan Emosional Terhadap Prestasi Belajar Siswa Kelas VIII Pada Mata Pelajaran IPA di SMP IT Cordova Samarinda - Sheryna Nur Khotimah; Akhmad Akhmad; Sri Purwati; Masitah Masitah (UNIB Press, 2026)
Emotional intelligence is one of the crucial elements that contribute to students' academic achievement. However, based on initial observations at SMP IT Cordova Samarinda, it was identified that the emotional regulation ability of some eighth-grade students has not reached an optimal level, although their academic achievement in science subjects is considered satisfactory. This study aims to examine the impact of emotional intelligence on student learning achievement in Natural Sciences at SMP IT Cordova Samarinda. This study applies a quantitative approach with an ex-postfacto correlational design, where the sample was selected through a purposive sampling technique and the data analysis used was simple linear regression with a significance level of 0.05. The findings from the simple linear regression test stated that the significance value (Sig.) reached 0.20, which exceeds 0.05. Therefore, it can be concluded that there is no influence of emotional intelligence on the learning achievement of eighth-grade students in Natural Sciences at SMP IT Cordova Samarinda, with an R Square value of 0.031, which concludes that emotional intelligence only contributes 3.1% to student learning achievement in that field.